STRATEGI KESOPANAN YANG DIGUNAKAN OLEH KARAKTER UTAMA DALAM FILM V FOR VENDETTA (Suatu Kajian Pragmatik) - Talolang, Ardiyanto (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT Language has a crucial role in a human life’s communication since it functions as a media tool to make interaction. One way to establish a meaningful conversation in society is by applying politeness. Behaving politely does not merely depend on how good a member in a society is, but also how to behave politely in daily conversation. This study is about politeness strategies used by the main character in "V for Vendetta" movie. This study used a descriptive method specifically using document analysis. The writer analyzed the utterances of V as the main character taken from the script of V for Vendetta movie and the writer also adopted politeness strategy’s theory proposed by Leech (1983). The finding show that are six kinds of maxim politeness which arrange the utterances. Those are The tact maxim, The generosity maxim, The approbation maxim, The modesty maxim, The agreement maxim, and The sympathy maxim. The function of politeness strategies is to reduce various kinds of conflict. With the strategy of politeness everything can run smoothly without any conflict.   Key word         : Politeness Strategies, The Main Character, V for Vendetta Movie